2004
DOI: 10.1124/jpet.103.064782
|View full text |Cite
|
Sign up to set email alerts
|

SL25.1131 [3(S),3a(S)-3-Methoxymethyl-7-[4,4,4-trifluorobutoxy]-3,3a,4,5-tetrahydro-1,3-oxazolo[3,4-a]quinolin-1-one], a New, Reversible, and Mixed Inhibitor of Monoamine Oxidase-A and Monoamine Oxidase-B: Biochemical and Behavioral Profile

Abstract: SL25.1131 [3(S),3a(S)-3 -methoxymethyl-7-[4,4,4-trifluorobutoxy]-3,3a,4,5-tetrahydro-1,3-oxazolo[3,4-a]quinolin-1-one] is a new, nonselective, and reversible monoamine oxidase (MAO) inhibitor, belonging to a oxazoloquinolinone series. In vitro studies showed that SL25.1131 inhibits rat brain MAO-A and MAO-B with IC 50 values of 6.7 and 16.8 nM and substratedependent K i values of 3.3 and 4.2 nM, respectively. In ex vivo conditions, the oral administration of SL25.1131 induced a dose-dependent inhibition of MAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Based on the results obtained for H 2 O 2 production, the effects of antioxidants and FCCP were evaluated after incubation of synaptosomes with the drugs at a fixed concentration (50 µM). The MAO inhibitors’ concentrations used in this study were selected from previous studies of MAO inhibition (Youdim et al ., 2001; Aubin et al ., 2004). The FCCP concentration used here was selected from studies of maximal mitochondrial depolarization in neurons (Oliveira and Gonçalves, 2009) and synaptosomes (Tretter et al ., 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results obtained for H 2 O 2 production, the effects of antioxidants and FCCP were evaluated after incubation of synaptosomes with the drugs at a fixed concentration (50 µM). The MAO inhibitors’ concentrations used in this study were selected from previous studies of MAO inhibition (Youdim et al ., 2001; Aubin et al ., 2004). The FCCP concentration used here was selected from studies of maximal mitochondrial depolarization in neurons (Oliveira and Gonçalves, 2009) and synaptosomes (Tretter et al ., 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Selective and non-selective MAO inhibitors have been developed for pre-clinical and clinical purposes, especially as treatments for major depression and Parkinson’s disease (Finberg and Youdim, 1983; Worms et al 1987; Pletscher 1991; Aubin et al 2004). The first MAO inhibitor to be discovered was the hydrazine derivative iproniazid, which was originally developed for the treatment of tuberculosis.…”
Section: Mao Mao Inhibitors and Amphetaminesmentioning
confidence: 99%
“…Aubin et al (2004) reported the behavioral profile of a newly developed, mixed-reversible MAO-A/B inhibitor, SL25.1131, in mice. The agent can improve decreased dopaminergic tone in the striatum by inhibiting MAO-A and –B and locomotion disrupted by treatment with MPTP (1-methyl-4-pheny l–1,2,3,6-tetrahydropyridine).…”
Section: Modification Of Meth Action By Non-selective Mao Inhibitorsmentioning
confidence: 99%
“…1,2 Galipinine (1; Figure 1), for example, has been isolated from Galipea officinalis trunk bark and exhibits activity against plasmodium falciparum, the protozoan parasite responsible of malaria; 3 the synthetic compound 2, known as SL 25.1131, is a reversible monoamine oxidase that is structurally related to befloxatone and has shown real therapeutic potential in the early phase of treatment against Parkinson's disease. 4 Virantmycin (3), an antiviral agent, also possesses a highly functionalized tetrahydroquinoline ring. 5…”
mentioning
confidence: 99%